화력 발전기 보일러 내부 작업자 위치 모니터링 시스템 개발 - 송규; K. Song; 윤찬녕; C. N. Yun; 신영하; Y. H. Shin; 신정훈; J. H. Shin; 한성희; S. H. Han; 장동영; D. Y. Jang (한국안전학회지, 2021)
There are regularly planned overhaul periods in thermal power plants, which involve the maintenance of the boiler of the power plants. However, thermal power plants workers are always exposed to risk during overhaul periods owing to the narrow space and significant dust inside the boiler. Therefore, it is essential to develop a safety monitoring system that is suitable for operating in this type of environment. In this study, we developed not only a worker three-dimensional (3D)-location monitoring system that can monitor and record the entry/exit of workers, their 3D-location, and fall accidents but also a method to secure the working environment and operation efficiency. This system comprises of a worker tag, which was equipped with an inertial measurement unit, a barometric pressure sensor, and a Bluetooth low energy (BLE), and the tags were given to each worker. In addition, the location of workers inside the boiler was measured using a pedestrian dead reckoning (PDR) method and BLE beacons. The location data of the workers tag were transmitted to the integrated database (DB) server through a gateway, and to the administrator monitoring system. The performance of the system was demonstrated inside an actual thermal power plant boiler, and the accuracy and reliability of the system were verified through a number of repeated tests. These results provide insights on designing a new system for monitoring enclosed spaces.